SETTLEMENT POPULATION HEALTH STUDIES IN JORONG BALAI OLI GUNUNG TALANG DISTRICT SOLOK REGION - Jamasri, Yogi; DRS. Bakaruddin, Ms, DRS. Bakaruddin, Ms; Nefilinda, Nefilinda (Pendidikan Geografi, 2014)
ABSTRACTÂ This study aimed to obtain, analyze and discuss the environmental health of settlements based livelihoods in Jorong Balai Oli Gunung Talang District Solok Region views of : housing conditions , clean water and water supply and landfills condition. This type of research is descriptive research. Population was all heads of families in Jorong Balai Oli Gunung Talang District Solok Region, amounting 212 households. Sample of respondents was taken by the head of household livelihoods proportional random sampling technique was used by 50% so that the respondent amounted to 106 households. Collecting data using guided inquiry, statistical analysis used was descriptive using percentage formula.The results is: 1) condition of houses in Jorong Balai Oli seen from the roof, walls, floors, source lighting, ventilation, a place to store food, storing food and where do MCK generally uniform, ie zinc roofs, stucco walls, cement floors, the source of electricity, ventilation is generally one for each room, store food in a clean, storing food in a clean and not separated and MCK activity in the private bathroom , 2 ) Provision of clean water source population consisted of clean water generally well used, clear water, fresh flavor, treatment of clean water reservoirs by means of draining clean water reservoirs, treatment performed 1 time in 1 week, and the distance of the source of clean water with sewage generally > 75 meters and 3) Provision of trash residents, residents always provide bins at home, dry and wet trash from plastic bags. Dry and wet waste separation is not the same. Residents generally take out the garbage every day, dumped into the clearing, trash containers provided by the government , and trash . Method of processing waste in the neighborhood generally burned